Spatial Analysis for Some UTP Campus Facilities for The Betterment of Their Services - Sazalli, Nurul Farhana (Universiti Teknologi PETRONAS, 2017)
A very well develop campus facilities can contribute to a healthy environment and a good lifestyle to campus students. Universiti Teknologi PETRONAS (UTP) main objective is to produce well-rounded students that can contribute to industry and also to the society. With an increasing number of students enrol and more courses introduced in UTP every year, more number of students will be using the facility and the locations of the facility becoming one of the matters of concern. This is due to the management will need to allocate student’s accommodation and set up class venue. Prior to that, an assessment will be done by using Spatial Analysis method in GIS (Geographic Information System) software to analyse UTP campus facilities which include student accommodation, café, academic blocks and other facilities for the betterment of their services. The analysis from this assessment will determine proposal steps for the betterment of their services as suggestion can be made to improve the serviceability for everyone’s benefit in the campus.